A cross‐cultural study of purchase intention of sponsored products based on American and Korean spectators of the 2010 FIFA World Cup South Africa. Issue 2 (2014) - ,; ,; ,
Abstract : Purpose – The purpose of this paper is: to explain the relative influence of attitude, subjective norm, and perceived behavioral control on purchase intention of the 2010 FIFA World Cup sponsored products; and to compare the purchase intention of American and Korean spectators toward sponsoring products of the 2010 FIFA World Cup. The structural equation modeling (SEM) revealed that subjective norm and perceived behavioral control were predictors of purchase intention. Further, multiple group analysis revealed that the path coefficient between subjective norm and purchase intention for the two groups was significantly different.Design/methodology/approach – A self‐administered questionnaire was developed to measure the four constructs of the theory of planned behavior (TBP) as well as demographic information. Upon completion of the psychometric properties test of the TPB, a SEM was conducted to examine the proposed hypotheses. The same fit indices as with the measurement model were adopted to evaluate the model fit. Finally, a multi‐group analysis was conducted to examine if the proposed relationships are different based on nationality (American vs Korean samples). A comparison of χ 2 value between unconstrained and constrained models was employed to assess whether the two groups are statistically different.Findings – SEM revealed that subjective norm and perceived behavioral control were predictors of purchase intention. In this study, a multi‐group analysis was conducted to examine if the proposed relationships in our model are different based on nationality. As a result, we found that two groups (i.e. American vs Korean) exhibited notable differences in subjective norms in determining purchase intentions of the 2010 FIFA World Cup sponsored products.Originality/value – Sponsors for mega sporting events, like the FIFA World Cup, must develop global marketing plans that appeal to worldwide audiences. Sport marketers, therefore, need cross‐cultural marketing analysis on equivalence and bias so that they better understand how spectators from different cultures behave after consuming the same event. Thus, application of the TPB in cross‐cultural studies aimed at understanding consumer intention after spectating the FIFA World Cup would provide marketers with valuable information for the formation of global marketing strategies.